Tamper-Resistant Optical Logic Circuits Based on Integrated Nanophotonics - Shiomi, Jun; Kotsugi, Shuya; Dong, Boyu; Onodera, Hidetoshi; Shinya, Akihiko; Notomi, Masaya (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
A tamper-resistant logical operation method based on integrated nanophotonics is proposed focusing on electromagnetic side-channel attacks. In the proposed method, only the phase of each optical signal is modulated depending on its logical state, which keeps the power of optical signals in optical logic circuits constant. This provides logic-gate-level tamper resistance which is difficult to achieve with CMOS circuits. An optical implementation method based on electronically-controlled phase shifters is then proposed. The electrical part of proposed circuits achieves 300 times less instantaneous current change, which is proportional to intensity of the leaked electromagnetic wave, than a CMOS logic gate.